2007
DOI: 10.1007/s00024-007-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Glacial-isostatic Adjustment and the Viscosity Structure Underlying the Vatnajökull Ice Cap, Iceland

Abstract: We examine the dependence of glacial-isostatic adjustment (GIA) due to changes in the Vatnajo¨kull Ice Cap, Iceland, on the underlying viscosity structure. Iceland offers a unique case study for GIA research, with a thinner elastic lithosphere underlain by a low-viscosity zone or asthenosphere, as opposed to regions such as Fennoscandia or North America described by a thicker lithosphere, while not necessarily featuring an asthenosphere.A laterally homogeneous spherical earth model is used consisting of an ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
3
20
1
Order By: Relevance
“…Effective viscosities calculated for individual Hawaiian xenoliths at their temperature of equilibration are > 10 −21 Pa.s (Figure ). These viscosities are at least 100 time higher than those estimated for the asthenosphere (2.7 × 10 −17 −2 × 10 −19 Pa.s, average ∼6 × 10 −18 Pa.s [ Craig and McKenzie , ; Hager , ; Pollitz et al ., ; Larsen et al ., ; Fleming et al ., ]. This result confirms that the oceanic mantle lithosphere is stronger than the asthenosphere, and that this is independent of its degree of metasomatism.…”
Section: Discussionsupporting
confidence: 84%
“…Effective viscosities calculated for individual Hawaiian xenoliths at their temperature of equilibration are > 10 −21 Pa.s (Figure ). These viscosities are at least 100 time higher than those estimated for the asthenosphere (2.7 × 10 −17 −2 × 10 −19 Pa.s, average ∼6 × 10 −18 Pa.s [ Craig and McKenzie , ; Hager , ; Pollitz et al ., ; Larsen et al ., ; Fleming et al ., ]. This result confirms that the oceanic mantle lithosphere is stronger than the asthenosphere, and that this is independent of its degree of metasomatism.…”
Section: Discussionsupporting
confidence: 84%
“…From GIA studies on Vatnajökull, researchers also found viscosity for upper mantle beneath Iceland lower than ~5 × 10 18 Pa s [ Sjöberg et al ., ; Fleming et al ., ; Jacoby et al ., ] that essentially indicates wet rheology [ Barnhoorn et al ., ]. However, the observed style of deformation in the Thingvellir graben fits well with the model prediction where strain rate is proportional to 3.5 order of the stress in a dry olivine rheology (Figure ) by satisfying other geophysical properties (see next section).…”
Section: Discussionmentioning
confidence: 99%
“…Since pre-LIA unloading is of little importance for modelling uplift rates in Iceland (Fleming et al 2007), we drive the Earth model by three different estimated ice unloading histories for Iceland, spanning from the LIA to 2012: (1) an Iceland-wide average annual mass balance is computed by tuning a simple degree-day mass balance model (Marzeion et al 2012) to existing records ) and forcing the model with weather station data from Stykkishólmur (1890-2010); (2) a local study for South-Iceland (A lgeirsdóttir et al 2011) is upscaled to reflect total, countrywide mass changes; (3) the known mass changes since the LIA of Langjökull ice cap ) are upscaled to reflect total, countrywide mass changes. All three unloading histories are calibrated to reproduce an estimate of the total ice mass loss of 500 Gt in Iceland between 1890 and 2012 (Björnsson & Pálsson 2008;Björnsson et al 2013).…”
Section: Glacial Isostatic Adjustmentmentioning
confidence: 99%